The Impact of Aphasia Camp on Partners of Persons with Aphasia - Selchow, Anna; Hoepner, Jerry K. (My University, 2018)
The purpose of this project was to study the experiences of close partners of persons with aphasia at the Chippewa Valley Aphasia Camp. Aphasia camps are an alternative service delivery model that addresses the needs of individuals impacted by the effects of chronic aphasia. Camps are designed to address common challenges of living with chronic aphasia. Research has found that both individuals with aphasia and their partners are at risk for social isolation. Therefore, partners also experience loss of their personal identity and a need for peer support. The effects of an aphasia camp experience on partners has only been examined in one prior study, which took place at the Aphasia Camp Northwest in Oregon. The present study investigated partner outcomes at the Chippewa Valley Aphasia Camp through a pre‐ and post‐ online Qualtrics survey. Questions examined demographic information and nature of interactions outside Posters Presentations: Social Sciences 105 of camp. Quantitative data includes tallies of the types of social interaction experiences that they engaged in before and after camp. Qualitative analyses of written responses yielded 10 pre-camp themes and 12 post-camp themes. In general, partners identified the value of camp, for themselves and their loved one with aphasia.
Color poster with text, charts, photographs, and graphs.
Keywords: Chippewa Valley Aphasia Camp; Aphasia; Interpersonal relations; Posters